Oxidative stress and antibody levels to periodontal bacteria in adults: the Nagasaki Islands study. (16th May 2013) - Tamaki, N; Hayashida, H; Fukui, M; Kitamura, M; Kawasaki, K; Nakazato, M; Maeda, T; Saito, T; Ito, H‐O
<x xml:space="preserve">Abstract</x> Objective Periodontitis is a chronic inflammatory disease of the tissues supporting the teeth and is caused by subgingival plaque. Systemic increases in reactive oxygen species are involved in pathogenesis of periodontitis. This study addressed the relationship between levels of serum oxidative stress and antibodies against putative periodontopathic bacteria and their association with periodontal conditions, in a community‐based study. Subjects and Methods Serum samples were measured for reactive oxygen metabolite (ROM) levels and anti‐oxidant capacity. The serum levels of immunoglobulin G (IgG) antibodies to Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi), Aggregatibacter actinomycetemcomitans (Aa), and Eikenella corrodens (Ec) were determined by ELISA. Results The participants with greater clinical attachment loss had higher serum ROM levels and IgG antibody titers to Pg. Serum ROM levels were positively correlated with antibody titers to Pg, Pi, and Ec. When the participants with greater probing pocket depth and clinical attachment loss were used as the dependent variables, high ROM levels showed a statistically significant associations in multivariate logistic analyses; the adjusted odds ratios were 2.9 (95% confidence interval = 1.0–8.5) and 6.0 (95% confidence interval = 2.0–17.6), respectively. Conclusions It was concluded that an increased oxidative stress may be detrimental to periodontitis in Japanese community‐dwelling adults.